2015
DOI: 10.4238/2015.august.14.16
|View full text |Cite
|
Sign up to set email alerts
|

Specialized features of the outer hair cell shapes in the cochlear fovea of bats

Abstract: ABSTRACT. In this study, we examined the specialized features of the outer hair cells (OHCs) and the stereocilium bundles of the bat cochlear fovea. Bat cochlea hair cells were observed by scanning and transmission electron microscopy, and the auditory brainstem response thresholds were assessed. The stereocilia bundles of the OHCs were extremely short. The OHC bodies were flask-shaped and cambiform or ball-shape in the cochlear fovea. Digitations in the Deiters cells had exaggerated lengths, and cup formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The results indicated that the stereocilium bundles of the outer hair cells were extremely short (about 0.8 µm). [ 291,292 ] The same short‐haired structure is also found in the outer hair cells of dolphin. [ 293 ] The lengths of stereocilia between striped dolphins and harbor dolphins are 1.8 and 0.8 µm, respectively.…”
Section: Biological Acoustic Sensilla and Bioinspired Acoustic Sensorsmentioning
confidence: 87%
“…The results indicated that the stereocilium bundles of the outer hair cells were extremely short (about 0.8 µm). [ 291,292 ] The same short‐haired structure is also found in the outer hair cells of dolphin. [ 293 ] The lengths of stereocilia between striped dolphins and harbor dolphins are 1.8 and 0.8 µm, respectively.…”
Section: Biological Acoustic Sensilla and Bioinspired Acoustic Sensorsmentioning
confidence: 87%